Pengolahan gas CO2 hasil samping industri amoniak melalui gasifikasi batubara yang telah dipirolisis dengan menambahkan Ca(OH)2 - Saripah sobah; Hary Sulistyo; Siti Syamsiah (Jurnal Rekayasa Proses, 2013)
CO2 is one of the greenhouse gases that is considered to cause global warming. Ammonia industry produces emission gas of CO2 in relatively great amount with an emission factor of 3.273 ton CO2/ton ammonia. One of the attempts to reduce CO2 gas emissions is by converting CO2 into syngas (CO) through gasification process. CO is one of the methanol feedstock. This research aimed to find out the amount of CO2 that can be reduced through charcoal gasification process. The reaction of carbon from coal can be reduced through the gasification process. Since the carbon reaction from coal with CO2 gas in the gasification process was an endothermic and occured very slowly at temperatures below 1000°C, Ca(OH) 2 was used as a catalyst. The coal gasification process was conducted in a fixed bed reactor. The experimental results showed that coal gasification with the use of Ca(OH) 2 in the pyrolysis process could reduce CO2 levels by 63.17%, meanwhile without Ca(OH) 2, the CO2 could be reduced only up to 35.2%.